Acoustics of Ducts and Mufflers. - Munjal, M. L. (Wiley, 2014)
Fully updated second edition of the premier reference book on muffler and lined duct acoustical performance Engine exhaust noise pollutes the street environment and ventilation fan noise enters dwellings along with fresh air. People have become conscious of their working environment. Governments of most countries have responded to popular demand with mandatory restrictions on sound emitted by automotive engines, and a thorough knowledge of acoustics of ducts and mufflers is needed for the design of efficient muffler configurations. This fully updated Second Edition of Acoustics of.